Management of tuberculosis risk, screening and preventive therapy in patients with chronic autoimmune arthritis undergoing biotechnological and targeted immunosuppressive agents - Picchianti-Diamanti, Andrea; Aiello, Alessandra; De Lorenzo, Chiara; Migliori, Giovanni Battista; Goletti, Delia (Frontiers in Immunology, 2025)
Tuberculosis (TB) is the leading cause of death in the world from an infectious disease. Its etiologic agent, the Mycobacterium tuberculosis (Mtb), is a slow-growing bacterium that has coexisted in humans for thousands of years. According to the World Health Organization, 10.6 million new cases of TB and over 1 million deaths were reported in 2022. It is widely recognized that patients affected by chronic autoimmune arthritis such as rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) have an increased incidence rate of TB disease compared to the general population. As conceivable, the risk is associated with age ≥65 years and is higher in endemic regions, but immunosuppressive therapy plays a pivotal role. Several systematic reviews have analysed the impact of anti-TNF-α agents on the risk of TB in patients with chronic autoimmune arthritis, as well as for other biologic disease-modifying immunosuppressive anti-rheumatic drugs (bDMARDs) such as rituximab, abatacept, tocilizumab, ustekinumab, and secukinumab. However, the data are less robust compared to those available with TNF-α inhibitors. Conversely, data on anti-IL23 agents and JAK inhibitors (JAK-i), which have been more recently introduced for the treatment of RA and PsA/AS, are limited. TB screening and preventive therapy are recommended in Mtb-infected patients undergoing bDMARDs and targeted synthetic (ts)DMARDs. In this review, we evaluate the current evidence from randomized clinical trials, long-term extension studies, and real-life studies regarding the risk of TB in patients with RA, PsA, and AS treated with bDMARDs and tsDMARDs. According to the current evidence, TNF-α inhibitors carry the greatest risk of TB progression among bDMARDs and tsDMARDs, such as JAK inhibitors and anti-IL-6R agents. The management of TB screening and the updated preventive therapy are reported.